Dream on - Hale, Shannon (Hale, Shannon. Dream on series, 2025)
"Something is missing from Cassie's life. Her parents don't have much money, she has to share her bedroom (and bed!) with her sisters, and her family never seem to have time for her. To make matters worse, her best friend Vali is always busy with a new friend. When Cassie gets a letter from a magazine sweepstakes with the words "YOU'RE THE WINNER" stamped on the front, she thinks it's the answer to all her problems. She could buy new furniture to replace their shabby old sofa. Or maybe a car so her family doesn't have to take two trips to go places. Or maybe she can make Vali her best friend forever by taking her on a fabulous vacation. The possibilities are endless, like an all-you-can-eat buffet! But will prizes really solve Cassie's problems? And what will she lose if she doesn't win anything at all?--